Acne and rosacea in skin of colour. (1st February 2022) - Maruthappu, T.; Taylor, M.
Summary: Acne and rosacea are common inflammatory skin conditions present in numerous racial and ethnic groups. There are distinct differences in clinical presentation, exacerbating factors, potential triggers and consequences of both conditions in individuals with skin of colour (SOC), classified as Fitzpatrick skin types III–VI. For example, acne can be complicated by the development of postinflammatory hyperpigmentation and keloid scarring in SOC, and this can influence treatment choice. Although rosacea is reported less frequently in SOC, this may be the result of delayed diagnosis or late presentation due to the difficulty in discerning the classic features of erythema in darker skin tones. In such cases, additional clues in the medical history and clinical examination may assist in making the diagnosis. This review aims to summarize nuances in both the diagnosis and management of these two common skin conditions in patients with SOC to support clinicians in providing an individualized treatment approach.